Pruning regimes and productivity of Eruca sativa Mill. in Anogeissus pendula Edgew. based agroforestry system - Singh, Prashant; Tripathi, V.D.; Shukla, Ashok; Prasad, Rajendra; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
In agroforestry systems, tree canopy hinders the sunlight required for proper growth and productivity of under-storey crops. Pruning of the canopy increases permeability of the sunlight, especially to crops growing beneath the canopy. In present study, effect of shoot pruning (0, 50 and 100% pruning) of Anogeissus pendula on its own growth and productivity of under-storey crop, Eruca sativa was investigated in a 20-years old agroforestry system. In the study, effect of distance from tree trunk (1.0 m and 2.0 m from tree base) on productivity of E. sativa was also assessed. Higher growth of A. pendula was recorded in un-pruned trees, followed by 50 and 100% pruned trees, which might be due to removal of live branches from the trees. Growth and productivity of E. sativa were significantly higher in pure crop treatment (control) than pruning plots. Among pruning regimes, maximum productivity was recorded in 100% pruning treatment, followed by 50 and 0% treatments (un-pruned). Thus, based on the results obtained from the study, it can be suggested that heavy pruning of A. pendula (100%) may be considered because it did not affect yield of E. sativa as much as affected 50% pruning treatment. Suitable canopy management in A. pendula will also reduce below-ground interactions, occurring between roots of trees besides supply of fuel wood along with crop produce.